2004
DOI: 10.1016/j.ydbio.2004.07.020
|View full text |Cite
|
Sign up to set email alerts
|

The epaxial–hypaxial subdivision of the avian somite

Abstract: In all jaw-bearing vertebrates, three-dimensional mobility relies on segregated, separately innervated epaxial and hypaxial skeletal muscles. In amniotes, these muscles form from the morphologically continuous dermomyotome and myotome, whose epaxial-hypaxial subdivision and hence the formation of distinct epaxial-hypaxial muscles is not understood. Here we show that En1 expression labels a central subdomain of the avian dermomyotome, medially abutting the expression domain of the lead-lateral or hypaxial marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
95
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 68 publications
10
95
0
1
Order By: Relevance
“…This finding suggests that En1 is the key marker for the beginning of epaxial-hypaxial segregation of the somite. Eventually, En1 expression also appears in the myotome, with the expression boundary aligned with the expression boundary in the overlying dermomyotome (Cheng et al, 2004). DiI-DiO labeling and quail-chick transplantation experiments indicated that all En1-expressing cells arise from the epaxial part of the somite (Cheng et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…This finding suggests that En1 is the key marker for the beginning of epaxial-hypaxial segregation of the somite. Eventually, En1 expression also appears in the myotome, with the expression boundary aligned with the expression boundary in the overlying dermomyotome (Cheng et al, 2004). DiI-DiO labeling and quail-chick transplantation experiments indicated that all En1-expressing cells arise from the epaxial part of the somite (Cheng et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…However, labeling experiments indicated that epaxial-hypaxial cells arise from distinct cell lineages during gastrulation (Selleck and Stern, 1991;Freitas et al, 2001;Eloy-Trinquet and Nicolas, 2002). Moreover, evidence from cell lineage restriction and cell sorting assays indicated that the mature dermomyotome and myotome comprises distinct epaxial and hypaxial compartments (Selleck and Stern, 1991;Freitas et al, 2001;Eloy-Trinquet and Nicolas, 2002;Cheng et al, 2004). Thus, an epaxial-hypaxial subdivision, although morphologically concealed, is present in the amniote somite.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations